2005
DOI: 10.2320/matertrans.46.64
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction of Sm from Chloride Solution with PC88A and Saponified PC88A

Abstract: In this study, solvent extraction experiments of Sm from a chloride solution with PC88A and with partially saponified PC88A were performed. The extraction reaction of Sm with PC88A was identified from the experimental data using a graphical method. A chemical model was then developed to predict the distribution coefficients of Sm for its extraction with the saponified PC88A. In the experimental ranges conducted in this study, the equilibrium constants for the solvent extraction of Sm with PC88A and with the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Compared to D2EHPA, PC88A is preferred for separating rare earth elements due to its high separation factor and high loading capacity [46], [47]. Thakur studied the extraction characteristics of the base metals Mn, Cu, Co and Ni by using the extractant 2-ethylhexyl phosphonic acid (PC 88A).…”
Section: Pc-88a Acid Extractantmentioning
confidence: 99%
“…Compared to D2EHPA, PC88A is preferred for separating rare earth elements due to its high separation factor and high loading capacity [46], [47]. Thakur studied the extraction characteristics of the base metals Mn, Cu, Co and Ni by using the extractant 2-ethylhexyl phosphonic acid (PC 88A).…”
Section: Pc-88a Acid Extractantmentioning
confidence: 99%
“…Acidic organophosphorous extractants such as D2EHPA and PC88A are widely used in the separation processes (Harada et al, 1971;Hoh and Bautista, 1979;Ioannou et al, 1972). Of these two extractants, PC88A is known to have a higher loading capacity and to yield higher separation factors (Lee et al, 2005). These acidic extractants have been widely used in the rare earth industry for the separation and purification (Preston and du Preez, 1990;Reddy et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Besides precipitation, several studies on solvent extraction as an effective route for separation of Sm were reported. Processing of a SmCo magnet for recovery of Sm and Co, and separation of Sm using CYANEX 572 from chloride leach liquor, was reported . The authors demagnetized the waste magnet by roasting at 1123 K prior to leaching with 4 M HCl at 368 K under 100 g/L S:L. Precipitated Sm and Co oxalates were calcined to produce oxides of Sm and Co.…”
Section: Introductionmentioning
confidence: 99%
“…The stripping efficiencies with HNO 3 , HCl, and CH 3 COOH as well as the thermodynamic functions of extraction were established. In continuation of Sm extraction from synthetic solution, Lee et al investigated the extraction of Sm from SmCl 3 solution using PC88A and saponified PC88A . The study involved estimation of equilibrium constants for both PC88A and saponified PC88A by analyzing ionic equilibria and prediction of distribution coefficients by developing a chemical model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation